ANALISIS KOMPARASI STORE ATMOSPHERE, LOKASI STORE DAN LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI EIGER ADVENTURE FLAGSHIP STPRE MERR SURABAYA DAN REI ADVENTURE MANYAR - Nadila Yulianita Devitri (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2023)
This study aims to determine the consumer profile of the Eiger Adventure Flagship Store Merr Surabaya and Rei Adventure Manyar, in addition to knowing whether there are differences in the store atmosphere, store location and service variables on purchasing decisions at the Eiger Adventure Flagship Store Merr Surabaya and Rei Adventure Manyar. This research uses quantitative methods. The sampling technique in this study was all consumers who had visited and shopped at EigerAdventure Flagship Store Merr Surabaya and Rei Adventure Manyar. The total samples in this study are 96 respondents. The data collection technique uses a questionnaire that has been tested using the Validity Test and Reliability Test. The data analysis technique in this study was the Independent Sample t-Test. The results of this study indicate that: (1) people who use Eiger and Arei products in terms of gender, there are 61 respondents (63.5%) male and female there are 35 respondents (36.5%), the majority as a student and the majority of income 2,000,000 – 3,500,000. (2) the independent variable store atmosphere, store location and service have differences on the dependent variable purchasing decisions.